MEMBANGUN KULTUR KEBEBASAN AKADEMI - Mufid, Mufid (Jurnal Bestari, 1992)
Academic Freedom can e regarded as the core spirit of unversity. It leads all human being which involved in this instutition to act based on the freedom of speech, the freedom of dialogue and the freedom of criticism. The right to publish many research findigs is another aspects of this concept. All students and lecturers are freely to do it without irrational interventaion or other kinds or threat. Five ages BC, Socrates proclaimed the spirit of academic freedom. His struggle againts government and sophist corruption led him to be a martyr. He was, however, remembered as the noted philosopher which his thought influenced modern philosphy. In the case of human relation to God, his philosophy insipired the dignity of human being. In the case of human relation of God, his philosopy inspired the dignity of human being. It is now called religious humanism. The nature of academic freedom refered to the truth of his philosophy.